Dumpy Mutations following X-Irradiation of DROSOPHILA MELANOGASTER Mature Sperm in Oxygen or in Nitrogen - Miyamoto, Tomio (1982)
A comparison was made of the oxygen enhancement pattern among the different kinds of dumpy mutations (olv, ov, ol, lv, o and v types), yellow mutations on the scute-8 chromosome, white, miniature and forked mutations, and the marker losses in the doubly marked Y chromosome [B(S) Y sc(8) (y(+))], all of which were induced by X rays in mature sperm of Drosophila melanogaster. The results indicate that (1) an essential difference does not exist in the oxygen enhancement pattern between the different kinds of dumpy mutations, except for the ov exceptions. For these exceptions, relatively high enhancement by oxygen is elucidated; (2) a similarity exists in the oxygen enhancement pattern among the different kinds of dumpy mutations (except for the ov exceptions), yellow, miniature and forked mutations, and B(S) and y(+) marker losses; and (3) the oxygen enhancement pattern elucidated for the ov exceptions is similar to that for the white mutations. These findings suggest that the nature of the different kinds of dumpy mutations is not different from one another, except for the ov exceptions, and that except for these ov exceptions and the white mutations, there seems to be some kind of similarity in the nature of mutation among the different kinds of mutations studied.